Sequence Logo Visualization based on Gestalt Perception – Novices vs Experts - Kok, Weiying; Oon, Y.B.; Lee, Nung Kion (2016)
Sequence logo is a popular graphical method for displaying the conservation characteristics of a sequence motif profile. Studies have found that decision making biases and misused of sequence logo occur due to the differences in individual perception, knowledge and experiences. The aim of this study is to identify the differences between the novices and experts in visualizing sequence logo based on Gestalt perception. 52 participants were involved in an online survey and independent t-test was used to analyse the data obtained. Results shown that there are significant differences in the perception and needs between novice and expert users. Visual cues and detailed information display are required by novice users whereas experts prefer a simple but more functional representation in the sequence logo. Therefore, it is essential to improve the sequence logo visualization in the colour, grouping, information display and interactivity of the tool in order to support the needs of various users.